2022
DOI: 10.3390/pharmaceutics14020369
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of RPMI 2650 and Calu-3 Cell Models for Evaluation of Nasal Formulations

Abstract: The RPMI 2650 and Calu-3 cell lines have been previously evaluated as models of the nasal and airway epithelial barrier, and they have demonstrated the potential to be used in drug permeation studies. However, limited data exist on the utilization of these two cell models for the assessment of nasal formulations. In our study, we tested these cell lines for the evaluation of in vitro permeation of intranasally administered drugs having a local and systemic effect from different solution- and suspension-based f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
(80 reference statements)
2
18
0
Order By: Relevance
“…FL treatment on-chip was able to reduce expression of inflammation and epithelial damage-associated genes, however it could not recover barrier damage induced by PHMG. One reason could be the small treatment window of 24 h which was not sufficient to recover major loss of barrier integrity by PHMG or booster doses of inhaled FL might be required to overcome such major damage ( Kortekaas Krohn et al, 2019 ; Sibinovska et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…FL treatment on-chip was able to reduce expression of inflammation and epithelial damage-associated genes, however it could not recover barrier damage induced by PHMG. One reason could be the small treatment window of 24 h which was not sufficient to recover major loss of barrier integrity by PHMG or booster doses of inhaled FL might be required to overcome such major damage ( Kortekaas Krohn et al, 2019 ; Sibinovska et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, they can be co-cultured with fibroblasts or endothelial cells, which can form a confluent monolayer and develop tight junctions as well. Thus, RPMI 2650 in a co-culture can be a reliable in vitro method for nasal drug absorption [92][93][94].…”
Section: Cell Culturementioning
confidence: 99%
“…Sibinovska et al. (2022) concluded that these cell lines can be applied to investigate the permeation of drugs that is administered IN, for both local and systemic effects, and from solution‐ or suspension‐based formulations.…”
Section: Models To Determine Intranasal Systemic and Nose‐to‐brain Dr...mentioning
confidence: 99%
“…The Calu-3 and RPMI 2650 cells were cultured under ALI to determine if these cell models have the ability to detect differences in drug absorption from different types of formulations such as solution-and suspension-based formulations. Both these cell models demonstrated a sufficient ability to distinguish and to show the effect of formulation composition on the permeability of various drugs Sibinovska et al (2022). concluded that these cell lines can be applied to investigate the permeation of drugs that is administered IN, for both local and systemic effects, and from solution-or suspension-based formulations.The MDCK cell line can be transfected with human ABCG2, in order for the cell line to express breast cancer resistance protein (BCRP) to investigate the influence of the BCRP transporter on the permeation of different drugs Gonçalves et al (2021).…”
mentioning
confidence: 98%